Use Public Tools for Career Success - Kaleba, Kermit; American Society for Training and Development (Infoline, 2006)
This publication unlocks the keys to finding and accessing public sector tools and grants that help training practitioners further their experience and skills. Included in this issue as well are tips on how to find obtain money-saving grants as well as how to use tax-relief methods for professional development opportunities.
Keywords: Employees : Training of; Career development; Grants-in-aid : United States; Tuition tax credits : United States